Direction of Trade Statistics Yearbook 2016. (Direction of Trade Statistics; Direction of Trade Statistics ;, 2016)
The 2016 yearbook issue of Direction of Trade Statistics provides, for about 160 countries, tables with current data (or estimates) on the value of imports from and exports to their most important trading partners. In addition, similar summary tables for the world, industrial countries, and developing countries are included. Reported data are supplemented by estimates whenever such data are not current or are not available in monthly frequency. Country pages include lines for all partner countries that have been reported, estimated, or extrapolated. It is sometimes assumed that corresponding export and import data between partner countries should be consistent. As a result of reporting and processing lags, trade data for a given period are often released before all customs documents for the period have been processed. These data are sometimes not revised, or, if data are revised, errors are nevertheless made in assigning the date on which goods are shipped or received and the late data are assigned to the wrong month, quarter, and/or year.